Hemostatic powder TC-325 in the management of upper and lower gastrointestinal bleeding: a two-year experience at a single institution - Chen, Yen-I; Barkun, Alan; Nolan, Sabrina (Endoscopy, 2015)
Background and study aims: TC-325 is a novel endoscopic hemostatic powder. Our aim was to describe a single-center experience with the use of TC-325 in the upper and lower gastrointestinal tract, while for the first time attempting to determine how long the powder remains on a lesion.Patients and methods: The charts of consecutive patients receiving TC-325 therapy between July 2011 and July 2013 were reviewed retrospectively. Primary endpoints included immediate hemostasis and early rebleeding (≤ 72 hours). Results: Overall, 60 patients received 67 treatments with TC-325: 21 for nonmalignant nonvariceal upper gastrointestinal bleeding, 19 for malignant upper gastrointestinal bleeding, 11 for lower gastrointestinal bleeding, and 16 for intra-procedural bleeding. Immediate hemostasis was achieved in 66 cases (98.5 %), with 6 cases (9.5 %) of early rebleeding. No serious adverse events were noted. No TC-325 powder was identified in the 11 patients who underwent second-look endoscopy, performed within 24 hours in 4 patients.Conclusions: TC-325 appears safe and effective for managing bleeding in the upper and lower gastrointestinal tract with a variety of causes. The time during which the powder remains in the gastrointestinal tract is short, with complete elimination from the gastrointestinal tract as early as within 24 hours after use.